Legal Certainty of Recognition of Customary Land in the National Legal System - Afnaini Afnaini; Hamdan Hamdan (Jurnal Restorasi : Hukum dan Politik, 2026)
Recognition of customary land has been accommodated in the Basic Agrarian Law (UUPA), but its implementation within the national legal system still faces challenges of dualism and legal uncertainty. This study aims to analyze the legal challenges of recognizing customary rights for indigenous communities and formulate comprehensive solutions to ensure legal certainty. The research method used is normative juridical with a statutory and conceptual approach. The results indicate that legal uncertainty stems from overlapping sectoral regulations (such as the Forestry Law, the Mining Law, and the Job Creation Law), biased indicators of the existence of customary rights, and the recognition mechanism in Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency No. 14 of 2024, which tends to be constitutive and bureaucratic because it requires a Regional Regulation (Perda). Consequently, the communal rights of indigenous communities are often marginalized by investment interests and national strategic projects. This study concludes that legal certainty can only be achieved through regulatory reconstruction that shifts the recognition paradigm to a declarative-confirmatory one, accelerates the ratification of the Indigenous Peoples Law, and integrates digital mapping of indigenous territories into the One Map Policy.